Personality characteristics and attributes of international medical graduates in general practice training: Implications for supporting this valued Australian workforce. (21st January 2016) - Laurence, Caroline O.; Eley, Diann S.; Walters, Lucie; Elliott, Taryn; Cloninger, Claude Robert
Abstract: Objectives: To describe the personality profiles of International Medical Graduates (IMGs) undertaking General Practice (GP) training in Australia. A better understanding of the personal characteristics of IMGs may inform their training and enhance support for their vital contribution to the Australian rural workforce. Design: Cross‐sectional self‐report questionnaires. Independent variables included socio‐demographics, prior training, the Temperament and Character Inventory, and the Resilience Scale. Setting and participants: GP registrars (IMGs = 102; AMGs = 350) training in the Australian General Practice Training rural and general pathway and the Australian College of Rural and Remote Medicine independent pathway. Main outcome measures: Univariate analysis explored the differences in levels of traits between IMG and AMG registrars. Results: Compared to the general population both groups have moderately high resilience, and well‐organised characters with high Self‐directedness, high Cooperativeness and low Self‐transcendence, supported by temperaments which were high in Persistence and Reward Dependence. IMGs were different than AMGs in two temperament traits, Novelty Seeking and Persistence and two character traits, Self‐directedness and Cooperativeness. Conclusions: Factors such as cultural and training backgrounds, personal and professional expectations, and adjustments necessary to assimilate to a new lifestyle and health system are likely to be responsible for differences found between groups. Understanding the personality profiles of IMGs provides opportunities for targeted training and support which may in turn impact on their retention in rural areas.